KOMUNIKASI TRANSENDENTAL RITUAL NGULAPIN DALAM PEMUJAAN IBU PERTIWI DENGAN SARANA WAYANG KLUPAK TIYING DI DESA ADAT JERO KUTA BATUBULAN - I Wayan Hendi Yasa; Relin D.E.; Made Sri Putri Purnamawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Transcendental communication is an interaction that is not real or real but has high spiritual power, such as the wayang klupak trying tradition, which is a spiritual activity that uses symbolic interactions to carry out transcendental communication. In this study, the problem raised in the ritual process of transcendental communication which has a microcosmic function or effect and also has a macrocosmic effect that is realized by continuing to carry out cultural traditions.This research is qualitative research, the data obtained included the form of sentences and descriptions. The theory used in this research is ritual communication theory, structural-functional theory, and transcendental communication theory. The data of this research are sourced from primary data and secondary data. The technique of determining informants used the snowball technique, data collection using interview techniques, and literature study. Data analysis techniques consist of data reduction, data presentation stage, and conclusion drawing stage. The novelty of this research includes the following: 1) the characters of Wayang Malen and Wayang Merdah are the main symbols in the ngulapin ritual of worshiping the motherland, to communicate transcendentally in order to be in harmony with nature. 2) mantra or sesontengan is a transcendental communication power for connecting in order to achieve physical and spiritual health in order to achieve the concept of tri hita karana. Even though technology has now mastered the world, the ancient cultural traditions of wayang klupak tiying in Batubulan village are still carried out by the local community because it is strongly believed that this noble cultural tradition has had a positive effect, and has also been proven to provide health and healing to local communities who continue to uphold the high tradition of this culture.